Strategies of South African banks expanding into Sub-Saharan Africa - Modiba, Matome (Graduate School of Business (GSB), 2019)
The Sub-Saharan African economic environment has experienced growth in the last two decades. This has led to capital inflows into the continent, which has meant that multinational companies have entered the market in search of growth and capital. Due to this, multiple banks have expanded their operations throughout Sub-Saharan Africa. The role that banks play on the African continent is vital as they provide a reliable conduit for capital to enter the market while also promoting economic growth in the countries in which they operate. As one of the largest economies on the continent, South Africa is home to the largest banks in Africa, many which have expanded their operations into the continent. This dissertation is a qualitative case study focusing on the expansion strategies used by some of the South African banks that expanded into SSA. The dissertation aimed to understand which entry strategies led to successful expansions, how the banks defined the success of the expansion as well as what challenges the banks experienced. The dissertation found that successful expansions are driven by the appetite, persistence and level of conviction within the organisation about their expansion strategy. The more consistent and ardent the financial intuition is regarding their strategy, the higher the possibility of achieving a successful expansion. The level of management and organisational support for the strategy, as well as the number of operations the institution established played a role. The financial investment that the organisation undertook for the expansion was also an important factor for success.